Campus outdoor environment, learning engagement, and the mental health of college students during the COVID-19 pandemic: From the perspective of students in different grades - Sun, Ning; Liu, Wanting; Zheng, Zhenhua (Frontiers in Public Health, 2023)
During the COVID-19, the mental health of Chinese university students has been a pressing concern. But the internal mechanism of perceived campus outdoor environment and learning engagement affecting college students’ mental health during the COVID-19 Pandemic has not been fully discussed. The current study used cross-sectional data from 45 Chinese universities to explore the relationship between perceptions of campus outdoor environments, learning engagement and college student mental health, and focused on differences among college students in different grades. Our study revealed the mental health problems of Chinese college students during the COVID-19 Pandemic were more severe. The mental health of postgraduates was generally poor, and their risk of depression was higher than that of undergraduates. More importantly, for postgraduates, the direct impact of perceived campus outdoor environment on their mental health was stronger. For undergraduates, the indirect impact of learning engagement on the effect of perceived campus outdoor environment on their mental health was stronger. The results of the study have implications for campus planners, landscape architects, and university planners to pay particular attention to the needs of postgraduates for campus outdoor environment, which is of great significance to improve the overall mental health of students during the COVID-19 Pandemic.